Organização de controle social na transição agroecológica do assentamento Pirituba - Silva, Fabiana Fagundes da (Universidade Federal de São Carlos, 2019)
The statutory participatory certification mechanism meets the expectations of a historical process of organic farming. The Organization and Social Control (OCS) is a tool that helps in the processes of agroecological transition, considered an advance for the development of agroecology in Brazil. In this sense, we seek to analyze the process of organic recognition through the OCS, noting its contribution to promote an agroecological transition from the redesign of agroecosystems in agrarian reform areas. The critical points of the process were applied based on the perception of the farmers, trying to understand how they create mechanisms to increase the sustainability of production systems. The methodology used was a Participating Action Research, and the investigation took place at OCS Agrovida linked to family groups in the Pirituba II Agrovilas I, V and VI Settlement in the southwest of Sao Paulo State. We consider that the economical perspective made significant progress towards processes of organic recognition of the agroecosystems. Finally, we conclude that the OCS and its socio-environmental tool allow us to visualize the challenges and actions for an agroecological transition starting with the redesigning of agroecosystems from collective perceptions.
Organization of social control in the agroecological transition of the Pirituba settlement
Keywords: Certificação participativa; Plano de manejo orgânico; Redesenho do agroecossistema; Participatory certification; Organic management plan; Agroecosystem redesign; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL